The systematic affinities between the Lower Cretaceous Ammonoidea Protacanthoplites abichi (Anthula, 1900) and Acanthohoplites aschiltaensis (Anthula, 1900) - Frau, Camille (European Journal of Taxonomy, 2023)
This work provides the first revision and illustration of the type material of the ammonite species Parahoplites abichi Anthula [Type species of Protacanthoplites Tovbina] and Parahoplites aschiltaensis Anthula [Type species of Acanthohoplites Sinzow] from the upper Aptian (Lower Cretaceous) of Dagestan, Russia. The close affinities and synonymy between these two species are confirmed, and Acanthohoplites aschiltaensis is here retained as the senior valid name by its long quoting history and its historical use as a zonal index of the upper Aptian. The genus Protacanthoplites should be thus synonymised with Acanthohoplites by priority in the date of publication. Comparison with, and distinction from, closely allied Acanthohoplitidae is provided.